Pengaruh Eco-Label, Eco-Brand Dan Green Trust Terhadap Green Purchase Intention Pada Lampu Philip Led - Ali Mujahidin (Jurnal Istiqro, 2020)
Nowdays the issue of the environment has become a major issue because many people are worried about environmental sustainability and this awareness continues to grow. So that many companies are competing to create environmental friendly products. This study aims to determine the effect of eco label, eco brand, and green trust on green purchase intention. The object of this study is lamp Philip LED. This study was conducted in Bojonegoro. The sampling method used in this research is non-probability sampling method with incidental sampling technique. Data were collected using questionnaire with likert scale, and a sample of 120 respondents has been collected. The data was analyzed using multiple linear regression analysis. The findings of this study revealed that: (1) eco label has a positive and significant effect on green purchase intention; (2) eco brand has a positive and significant effect on green purchase intention; (3) green trust has a positive and significant effect on green purchase intention.